Pharmacokinetic model‐guided enoxaparin dosing in the Neonatal ICU: Retrospective cohort study to plan for prospective feasibility trial - Haden Bunn; Catherine Schentag; Leonardo R. Brandão; Vijay Ivaturi; Tamorah Lewis (Wiley, 2024)
Abstract Traditional milligram per kilogram (mg/kg) dosing of enoxaparin in neonates frequently fails to achieve target anti‐Xa levels promptly, necessitating repeated laboratory monitoring and dose adjustments. This study investigated whether a personalized dosing strategy based on predicted individual clearance and volume of distribution could improve outcomes, comparing standard‐of‐care (SOC) mg/kg dosing to pharmacokinetic (PK) model‐informed precision dosing (MIPD). A retrospective analysis was conducted on hospitalized neonates treated with enoxaparin at less than 44 weeks postmenstrual age from 2019 to 2022. Data on demographics, drug dosing, PK model covariates, and clinical outcomes were extracted from electronic health records and analyzed using the Pumas‐AI Lyv dosing tool. The primary focus was on comparing the initial SOC dose to the MIPD‐recommended dose. The secondary outcome measured was the time required to achieve therapeutic anti‐Xa levels. The study included 168 neonates with a median postnatal age of 15 days (range 1-149) and a median dosing weight of 3.1 kg (range: 0.82-5.2). MIPD‐recommended initial doses were 20%-60% higher than SOC doses in 32% of the cases and over 60% higher in 11% of cases. Neonates who received SOC doses that were much lower than the MIPD recommendation showed the longest delays in reaching therapeutic anti‐Xa levels. The results indicate that PK model‐informed of enoxaparin dosing leads to higher initial dosages than SOC in neonates, potentially reducing the time to therapeutic anti‐Xa levels. These findings are being utilized to define dosing limits for a prospective trial of MIPD in neonatal intensive care settings.